Toxicity of lead and mancozeb differs in two monophyletic Daphnia species - Araujo, G. S.; Pinheiro, C.; Pestana, J. L. T.; Soares, A. M. V. M.; Abessa, D. M. S. [UNESP]; Loureiro, S. (Elsevier B.V., 2019)
Lead and mancozeb are two important chemicals used for different human purposes and activities worldwide. Hazard assessment in different areas of the world is carried out with different but phylogenetically similar species, adapted to different climatic conditions, in order to increase relevance. This study evaluated the sensitivity of two monophyletic species, the tropical species Daphnia similis and the temperate species Daphnia magna, to the two chemicals lead and mancozeb. Standard acute and chronic ecotoxicological tests (reproduction and growth), as well as other sublethal measurements such as the intrinsic rate of population increase (r), feeding rate (FR) and O-2 consumption, were recorded along with the analysis of the AChE activity to determine the neurotoxicity of both contaminants. Albeit their similar evolutionary status, D. magna generally presented a lower sensitivity to Pb in comparison to D. similis. Despite the differences in sensitivity, both species presented similar patterns of response under Pb exposure, with diminished reproductive outputs, feeding impairment, reduced O-2 consumption and no effect on AChE activity. Mancozeb decreased the reproduction, rate of population increase and feeding rate, increased the AChE activity in both species and increased O-2 consumption only in D. magna. While D. magna increased O-2 consumption under mancozeb exposure, no effects were observed for D. similis. Thus, species may present different responses and sensitivities to different pollutants, regardless of their phylogeny. Therefore, the use of ecotoxicological assays with native species is crucial for a better ecological risk assessment in contaminated areas.
Keywords: Daphnids; Metal; Fungicide; Acute toxicity; Chronic toxicity; Acetylcholinesterase